Protective properties of inhaled IL-22 in a model of ventilator-induced lung injury - Frank, Sandra; Bachmann, Malte; Scheiermann, Patrick; Goren, Itamar; Hofstetter, Christian; Pfeilschifter, Josef; Zwissler, Bernhard; Muhl, Heiko (American journal of respiratory cell and molecular biology, 2011)
High-pressure ventilation induces barotrauma and pulmonary inflammation, thus leading to ventilator-induced lung injury (VILI). IL-22 has both immunoregulatory and tissue-protective properties. Functional IL-22 receptor expression is restricted to nonleukocytic cells, such as alveolar epithelial cells. When applied via inhalation, IL-22 reaches the pulmonary system directly and in high concentrations, and may protect alveolar epithelial cells against cellular stress and biotrauma associated with VILI. In A549 lung epithelial cells, IL-22 was able to induce rapid signal transducer and activator of transcription (STAT)-3 phosphorylation/activation, and hereon mediated stable suppressor of cytokine signaling (SOCS) 3 expression detectable even 24 hours after onset of stimulation. In a rat model of VILI, the prophylactic inhalation of IL-22 before induction of VILI (peak airway pressure = 45 cm H2O) protected the lung against pulmonary disintegration and edema. IL-22 reduced VILI-associated biotrauma (i.e., pulmonary concentrations of macrophage inflammatory protein-2, IL-6, and matrix metalloproteinase 9) and mediated pulmonary STAT3/SOCS3 activation. In addition, despite a short observation period of 4 hours, inhaled IL-22 resulted in an improved survival of the rats. These data support the hypothesis that IL-22, likely via activation of STAT3 and downstream genes (e.g., SOCS3), is able to protect against cell stretch and pulmonary baro-/biotrauma by enhancing epithelial cell resistibility.
Gesehen am 29.07.2022